Increasing Dominance - the Role of Advertising, Pricing and Product Design - Tobias Kretschmer; Mariana Rösner (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2010)
Despite the empirical relevance of advertising strategies in concentrated markets, the economics literature is largely silent on the effect of persuasive advertising strategies on pricing, market structure and increasing (or decreasing) dominance. In a simple model of persuasive advertising and pricing with differentiated goods, we analyze the interdependencies between ex-ante asymmetries in consumer appeal, advertising and prices. Products with larger initial appeal to consumers will be advertised more heavily but priced at a higher level - that is, advertising and price discounts are strategic substitutes for products with asymmetric initial appeal. We find that the escalating effect of advertising dominates the moderating effect of pricing so that post-competition market shares are more asymmetric than pre-competition differences in consumer appeal. We further find that collusive advertising (but competitive pricing) generates the same market outcomes, and that network effects lead to even more extreme market outcomes, both directly and via the effect on advertising.
urn:nbn:de:bvb:19-epub-11500-6
Keywords: 650; Werbung; Mark-up Pricing; Produktgestaltung; Duopol; Netzwerkökonomik